Effective cancer immunotherapy combining mRNA-encoded bispecific antibodies that induce polyclonal T cell engagement and PD-L1-dependent 4-1BB costimulation - Hangiu, Oana; Navarro, Rocío; Frago, Susana; Rubio-Pérez, Laura; Tapia-Galisteo, Antonio; Díez-Alonso, Laura; Gómez-Rosel, Marina; Silva-Pilipich, Noelia; Vanrell, Lucía; Smerdou, Cristian; Howard, Kenneth A.; Sanz, Laura; et al. (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors have revolutionized cancer therapy, but many patients fail to respond or develop resistance, often due to reduced T cell activity. Costimulation via 4-1BB has emerged as a promising approach to enhance the effector function of antigen-primed T cells. Bispecific T cell-engaging (TCE) antibodies are an effective way to provide tumor-specific T cell receptor-mediated signaling to tumor-infiltrating lymphocytes. mRNA-based delivery of bispecific antibodies, offer a novel approach to enhance tumor-specific immune responses while minimizing adverse effects.MethodsTwo bispecific antibodies were generated: the EGFR x CD3 TCE antibody (LiTE) and the PD-L1 x 4-1BB costimulatory antibody (LiTCo), which was further fused to a high FcRn albumin variant (Albu-LiTCo). The mRNA encoding these bispecific antibodies contains an N1-methylpseudouridine modified nucleoside and regulatory sequences to ensure proper expression and stability. A series of in vitro assays and cell-based analyses were performed to characterize both antibodies. The in vivo efficacy of the mRNA-encoded bispecific antibodies was evaluated in xenograft tumor models expressing EGFR.ResultsWe investigated the combined effect of two mRNA-encoded Fc-free bispecific antibodies with complementary mechanisms of action: an EGFR-targeting TCE and a half-life extended PD-L1 x 4-1BB costimulatory antibody. The mRNAs encoding both bispecific LiTERNA and Albu-LiTCoRNA, showed similar binding specificity and in vitro function to their protein analogues. Pharmacokinetic studies demonstrated sustained expression of both bispecific antibodies following intravenous administration of the mRNAs formulated using a polymer/lipid-based nanoparticle (LNP) but different pharmacokinetic profiles, shorter for the TCE and longer for the PD-L1 x 4-1BB. When administered as a mRNA-LNP combination (ComboRNA), the growth of EGFR-positive tumors in immunocompetent mice was significantly inhibited, resulting in tumor regression in 20% of cases with no associated toxicity. Histological analysis confirmed increased T cell infiltration in the tumors treated with LITERNA and ComboRNA. Repeated administration resulted in sustained production of bispecific antibodies with different exposure cycles and potent antitumor activity with a favorable safety profile.ConclusionsThese results highlight the potential of combining two mRNA-encoded bispecific antibodies with different mechanisms of action and programmable half-life for cancer immunotherapy.